The Influence of Operating Cash Flow Opacity, Institutional Ownership, and Audit Quality on Stock Price Crash in Non-Financial Companies Listed on the Indonesian Stock Exchange - Suhani, Nindya; Arfan, Muhammad; Saputra, Mulia (East Asian Journal of Multidisciplinary Research, 2024)
This research aims to examine the influence of operating cash flow opacity, institutional ownership, and audit quality on stock price crashes. The population for this study consists of non-financial companies listed on the Indonesia Stock Exchange that experienced a stock price crash in 2020. The sample consisted of 178 companies selected using simple random sampling techniques. The data used in this research is secondary data obtained from the company's annual report and the stock price list on the Indonesia Stock Exchange and analysed using the regression analysis method. Empirical results show that operating cash flow opacity and institutional ownership are positively related to stock price crashes, while audit quality has a negative effect on stock price crashes.